2018
DOI: 10.7547/15-106
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Efficacy of Extracorporeal Shockwave Therapy for Plantar Fasciitis with Magnetic Resonance Imaging Findings

Abstract: Extracorporeal shockwave therapy is a safe and effective treatment that yields favorable results in improvement of pain and function for plantar fasciitis. An MRI is useful for determining response to ESWT for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
0
8
0
2
Order By: Relevance
“…A similar trend was observed by Mróz et al [36], Drużbicka et al [35], Krzentowska et al [10], or Hołubowicz [37], who also observed a significant relief of pain measured with the VAS scale in their research. A significant relief of pain after the shock wave therapy was also observed by Yalcin et al [38], Gerdesmeyer et al [39], Bicer et al [40], Purcell et al [41] or Hocaoglu et al [42]. Rompe et al [43] present another opinion on the effects of shock wave therapy in the short term.…”
Section: Discussionmentioning
confidence: 58%
“…A similar trend was observed by Mróz et al [36], Drużbicka et al [35], Krzentowska et al [10], or Hołubowicz [37], who also observed a significant relief of pain measured with the VAS scale in their research. A significant relief of pain after the shock wave therapy was also observed by Yalcin et al [38], Gerdesmeyer et al [39], Bicer et al [40], Purcell et al [41] or Hocaoglu et al [42]. Rompe et al [43] present another opinion on the effects of shock wave therapy in the short term.…”
Section: Discussionmentioning
confidence: 58%
“…Em relação a frequência utilizada houve variação, sendo de 4 Hz 17 , 15 Hz 12,16 e com vários estudos com 10 Hz 14,15,18-,22 .…”
Section: Resultsunclassified
“…Em nove dos dez estudos, a intervenção para tratamento da dor na FP com utilização da TOC mostrou resultados significativos 12,[14][15][16][17][18][19][20][21][22] . Com relação aos instrumentos para avaliação quantitativa da dor, todos os estudos utilizaram a EVA 12,[14][15][16][17][18][19][20][21][22] . Consiste em uma linha de dez centímetros, que possui em geral, as frases "ausência de dor e dor insuportável", apresentada em uma folha em branco, numerada de zero (ausência), a dez (dor insuportável).…”
Section: Resultsunclassified
“…Once more, these findings are also contrary to what is reported in previous studies of conservative treatment in acute cases or even chronic evolution from the onset of plantar fasciitis symptoms. 3,19 Those authors reported changes in the qualitative variables after conservative treatment. The majority of them used shock wave therapy.…”
Section: Discussionmentioning
confidence: 99%